Molecular Insights into The Role of Non-Coding Rnas in The Pathogenesis and Progression of Human Diseases: A Review Article - Farah mumtaz; Dhamyaa Obaid Shalgam; Shaima Basil Salman; Ali A. Al-fahham (International Journal of Medical Science and Dental Health, 2025)
The ncRNAs don’t change the central dogma, but rather they tell us that non-protein coding parts of the genome are actually essential in controlling expression and functions of genes at the cellular level. The paper covers major classes of ncRNAs comprising housekeeping RNAs, microRNAs, small interfering RNAs, piwi-interacting RNAs, small nucleolar RNAs, small nuclear RNAs, long non-coding RNAs, and circular RNAs with diverse mechanisms of actions. More detailed descriptions are provided for ncRNA function in human health and disease: cancer; cardiovascular diseases; and neurological disorders. Herein they can be oncogenes and tumor suppressors or critical modulators in pathophysiological processes. This work highlights diagnostic as well as prognostic potentials based on circulating ncRNAs which are relatively novel non-invasive biomarkers that have gained much attention lately. Among therapeutic strategies discussed is one that includes direct miRNA replacement through synthetic miRNA mimics and antagomiRs plus antisense oligonucleotides as inhibitors of ncRNA function. The article also sets out current challenges and future directions for clinical application of research findings relating to ncRNAs even while underscoring their promise as key effectors in precision medicine.